Vibration safety evaluation model and sensor network-based monitoring system for coke drums in operation. Issue 3 (4th May 2023) - Choi, Jewoo; Kang, Deok Shin; Lee, Min Gyu; Bae, Sang Geun; Hong, Taehoon; Lee, Dong-Eun; Park, Hyo Seon
ABSTRACT: Repetitive and severe thermal loads and load changes affect not only the physical properties of the coke drum but also its dynamic properties, possibly leading to structural failure. In particular, the operation weight of the drum, which increases up to 10 times or more, affects the dynamic properties of the structure and may threaten safety. Therefore, a vibration safety evaluation model for coke drums in operation is proposed to provide critical feedback on damage accumulation and to evaluate the vibration stability. A monitoring system was also developed to validate the model predictions by measuring the vibration patterns and corresponding modal parameters of the coke drums in operation. The proposed technique was applied to two coke drums in operation, and the vibration safety and factors causing vibration in the target structures were analyzed. The maximum vibration pattern was observed in the target structures at a feeding ratio of 71%. It exceeded the vibration criteria of the vibration safety evaluation model by up to 406%. Moreover, the analysis determined that the rapid increase in operating weight of the coke drums due to the influx of heavy crude oil, and the down-shift in their mode frequency induced superimposition and resonance with the structural mode, causing vibration.